2022
DOI: 10.1101/2022.03.14.484305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent lipid droplet-rich microglia worsen stroke outcome in old mice

Abstract: Microglial cells of the aged brain manifest signs of dysfunction that could contribute to the worse neurological outcome of stroke in the elderly. Treatment with colony-stimulating factor-1 receptor antagonists enable transient microglia depletion that can be followed by microglia repopulation after interruption of the treatment, causing no known harm to mice. Using this strategy, we aimed to restore microglia function and ameliorate stroke outcome in aged mice. Cerebral ischemia/reperfusion induces strong inn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, preliminary evidence reported in a recent preprint indicates that ischemia triggers lipid accumulation in microglia of young mice, promoting premature aging of microglia [237]. Lipid droplet accumulation has been reported to be a feature of aged microglia [238] and it has been suggested that after stroke, an increase of lipid droplets in microglia may contribute to poor stroke outcome in old mice [237]. Given that this effect might be attributable to phagocytosis of cell debris due to brain injury leading to intracellular accumulation of lipids in microglial cells, this further links the inflammatory response in stroke to mitochondrial metabolism as well as lipophagy (see above).…”
Section: Metabolic Regulation Of Immune Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, preliminary evidence reported in a recent preprint indicates that ischemia triggers lipid accumulation in microglia of young mice, promoting premature aging of microglia [237]. Lipid droplet accumulation has been reported to be a feature of aged microglia [238] and it has been suggested that after stroke, an increase of lipid droplets in microglia may contribute to poor stroke outcome in old mice [237]. Given that this effect might be attributable to phagocytosis of cell debris due to brain injury leading to intracellular accumulation of lipids in microglial cells, this further links the inflammatory response in stroke to mitochondrial metabolism as well as lipophagy (see above).…”
Section: Metabolic Regulation Of Immune Cellsmentioning
confidence: 97%
“…Furthermore, preliminary evidence reported in a recent preprint indicates that ischemia triggers lipid accumulation in microglia of young mice, promoting premature aging of microglia [237]. Lipid droplet accumulation has been reported to be a feature of aged microglia [238] and it has been suggested that after stroke, an increase of lipid droplets in microglia may contribute to poor stroke outcome in old mice [237].…”
Section: Metabolic Regulation Of Immune Cellsmentioning
confidence: 99%
“…Alzheimer's disease neurons, glia, myeloid cells, ependymal cells, astrocytes [319][320][321][322][323] Parkinson's disease neurons, microglia [319,324,325] Age-related macular degeneration retinal pigment epithelium [326] Stroke microglia [327] Atherosclerosis Foam cells [328,329] Cardiovascular disease myocardium [330,331] Sarcopenia muscle cells [332,333] Rheumatoid arthritis T-cells [334] Chronic obstructive pulmonary disease (COPD) macrophages [327] Periodontitis monocytes, macrophages [335,336] Osteopenia osteoblasts, osteocytes [337,338] Osteoarthritis chondrocytes, cartilage [339][340][341] Diabetes β-cells [342,343] Liver disease (NAFLD) 1 parenchymal hepatocytes [344] 2…”
Section: Disease Main Affected Cell Type/tissue Referencesmentioning
confidence: 99%
“…For example, Elmore et al demonstrated this shift using a colony-stimulating factor 1 receptor inhibitor to noninvasively eliminate senescent microglia, discontinue the drug, restimulate the proliferation of new microglia in the senescent brain, and reverse cognitive, synaptic, and neuronal deficits in aging mice [ 75 ]. Recent investigations have shown that aging brains accumulate lipid droplets in the microglia after stroke, possibly due to impaired phagocytosis, exacerbated innate immune responses, and increased expression of certain lipid droplet-associated proteins [ 76 , 77 ]. Defective phagocytosis results in the excessive production of ROS and proinflammatory cytokines [ 78 ].…”
Section: Aging-related Immune System Alterations In Strokementioning
confidence: 99%